Mitochondrial genetic variation and population structure of the striped snakehead, Channa striata in Malaysia and Sumatra, Indonesia. (June 2015) - Tan, M.P.; Jamsari, A.F.J.; Muchlisin, Z.A.; Siti Azizah, M.N.
Abstract: We explored the genetic diversity and structure of the striped snakehead ( Channa striata ) across Malaysia and Sumatra (Indonesia) using the partial mtDNA CO1 gene. Twenty five populations (n = 345) were assayed and subdivided into six regions, following the physiogeographical barriers. Populations Sega (SG), Tanjung Tambutan (TR), Kajang (KJ) and Linggi (LG) are highly diversified (Hd: 0.484–0.762, π: 0.0033–0.0059) which could serve as candidates for a selective breeding programme. The only population that contributed to the total allelic richness is Takengon (CS) as it is highly differentiated from other populations and genetically variable within population. We detected two major phylogenies: 1) northwest Peninsular Malaysia and 2) all other regions of Malaysia and Sumatra, Indonesia. They are products of the physical restriction to gene flow between the two lineages by the Bintang Mountain Range. A total of 92.4% of the population pairwise comparison FST showed significant structuring, yet several geographically distant populations showed a close genetic relationship. The discrepancy is due to ancient population dispersal and human-mediated translocation. These major findings provide an important base study for initiating a selective breeding program. The high population genetic diversity requires independent conservation as they contain most of the total diversity in this area. Highlights: We investigate population genetics of Channa striata from Malaysia and Indonesia. The populations were genetically highly diversified. Bintang Mountain Range restricted gene flow between two major phylogenies. Geographically distant populations were genetically closely related. The discrepancy was due to ancient dispersal and human mediated translocation.